Amnesia of inhibitory avoidance by scopolamine is overcome by previous open-field exposure - Colettis, Natalia Claudia (2014)
The muscarinic cholinergic receptor (MAChR) blockade with scopolamine either extended or restricted to the hippocampus, before or after training in inhibitory avoidance (IA) caused anterograde or retrograde amnesia, respectively, in the rat, because there was no long-term memory (LTM) expression. Adult Wistar rats previously exposed to one or two open-field (OF) sessions of 3 min each (habituated), behaved as control animals after a weak though over-threshold training in IA. However, after OF exposure, IA LTM was formed and expressed in spite of an extensive or restricted to the hippocampus MAChR blockade. It was reported that during and after OF exposure and reexposure there was an increase in both hippocampal and cortical ACh release that would contribute to “prime the substrate,” e.g., by lowering the synaptic threshold for plasticity, leading to LTM consolidation. In the frame of the “synaptic tagging and capture” hypothesis, plasticity-related proteins synthesized during/after the previous OF could facilitate synaptic plasticity for IA in the same structure. However, IA anterograde amnesia by hippocampal protein synthesis inhibition with anisomycin was also prevented by two OF exposures, strongly suggesting that there would be alternative interpretations for the role of protein synthesis in memory formation and that another structure could also be involved in this “OF effect.”